Synthesis and properties alkylderivatives of 5-(((5-amino-1,3,4-thiadiazole-2-yl)thio)methyl)-4-phenyl-1,2,4-triazole-3-thione - Fedotov, S. O.; Hotsulia, A. S.; Федотов, Сергій Олегович; Гоцуля, Андрій Сергійович (Харків : НФаУ, 2021)
The development of new biologically active compounds involves the directed construction of molecules based on basic fragments, which include 1,3,4-thiadiazole and 1,2,4-triazole rings with a wide range of pharmacological activity. The search for new drugs is due to the presence of unwanted side effects, the acquisition of resistance, high toxicity and more. Therefore, the development of new drugs with minimal side effects and low toxicity is relevant to modern pharmaceutical practice. The purpose of the work was to study the reaction of nucleophilic substitution of 5-((5-amino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole-3-thione with haloalkanes and to establish the structure of the obtained compounds.